Kajian Kepemilikan Keluarga pada Perusahaan Initial Public Offering Tahun 2022 di Bursa Efek Indonesia - Gadeng, Tarmizi; Rusnaidi; Zulkifli Umar; Sofia, Ayya (Forum Kerjasama Pendidikan Tinggi, 2023)
This researcher aims to examine family ownership in companies that have an Initial Public Offering in 2022 on the Indonesian Stock Exchange. This study includes the characteristics of family ownership, the portion of family ownership either directly or indirectly, and the ultimate beneficial owner. This type of research is qualitative. This study observes companies that have Initial Public Offerings on the Indonesia Stock Exchange in 2022, totaling 15 companies. The data used in this study is secondary data, namely in the form of company prospectus reports published on the Indonesia Stock Exchange. The data analysis technique used is descriptive method. The results of this study found that 9 out of 15 companies that had an Initial Public Offering on the Indonesia Stock Exchange in 2022 were owned by families, either directly or indirectly. Ownership by the family, namely having the characteristics of a married couple, and siblings. The portion of family ownership dominates in the 9 companies observed, ownership is owned directly or indirectly through other companies formed. Likewise, the ultimate beneficial owner of the company is dominated by family ownership.